Too soon to switch? Early TKI switching vs. continuous monotherapy: long-term outcomes in chronic myeloid leukemia - Megiso, Muluken; Ugwu, Chidiebube; Obomanu, Elvis; Taneja, Alankrita (Frontiers in Hematology, 2026)
BackgroundEarly switching of tyrosine kinase inhibitors (TKIs) in chronic myeloid leukemia (CML), particularly within the first 3 months of initiation, may indicate intolerance or suboptimal response. However, the long-term clinical impact of such early modifications remains uncertain. This study compares outcomes between patients who switched early and those who remained on their initial TKI.MethodsWe used data from the TriNetX US Collaborative Network to compare matched cohorts of early switchers and long-term non-switchers for imatinib (n=349 vs. n=4,579), dasatinib (n=377 vs. n=2,849), and nilotinib (n=114 vs. n=1,308). Patients were followed for 3 and 5 years. Outcomes included mortality, cardiovascular complications, diabetes, thromboembolic events, hospitalizations, and ICU admissions. The analysis period began immediately after the TKI switch for switchers. To minimize bias and ensure correct outcome attribution, patients who had any of the outcomes before switching were excluded from both cohorts. Propensity matching and logistic regression were applied to estimate risk ratios (RRs) with 95% confidence intervals (CIs).ResultsEarly switch from imatinib was associated with significantly higher 5-year mortality (24.0% vs. 11.9%; RR = 2.03, 95% CI 1.43–2.87, p < 0.001). Increased rates of heart failure were observed at both 3 years (10.8% vs. 5.4%; RR = 1.99, p = 0.015) and 5 years (12.1% vs. 7.3%; RR = 1.65, p = 0.046), alongside higher hospitalization (27.9% vs. 16.5%; p = 0.019) and ICU admissions (11.9% vs. 7.0%; p = 0.033). Dasatinib early switchers had worse 5-year mortality (21.1% vs. 14.0%; RR = 1.51, p = 0.011) and more frequent heart failure at 3 years (12.1% vs. 6.7%; RR = 1.80, p = 0.020). ICU admission was also significantly elevated at both 3 years (17.3% vs. 9.2%) and 5 years (19.9% vs. 10.3%; RR = 1.88, p = 0.002). Among nilotinib users, early switching resulted in a non-significant increase in 5-year mortality (20.2% vs. 11.5%; RR = 1.75, p = 0.074) but was linked to significantly higher ICU admissions at 5 years (19.4% vs. 9.3%; RR = 2.10, p = 0.033).ConclusionsEarly switching from first-line TKI therapy in CML is consistently associated with worse survival and greater complication rates across multiple agents. These results emphasize the need for cautious decision-making and close monitoring when considering early changes to frontline therapy.